Reality of implementation, barriers, and local-based innovations of stunting reduction programs in Papua region, Indonesia: A systematic review - Mustasmara, Rida; Hariyanti, Tita; LPH. Mastuti, Ni (Narra J, 2026)
Stunting remains a major public health problem in Indonesia, with a disproportionate burden in Papua, where many districts are classified as 3T regions (frontier, outermost, and least-developed areas) characterized by limited infrastructure, restricted access to services, and distinct socio-cultural challenges. The aim of this study was to comprehensively examine the implementation of stunting reduction programs in Papua’s 3T regions, including program delivery, barriers, and local innovations, through a systematic review. Articles were identified through searches of five major databases and grey literature and were selected using the PRISMA framework. Eligible studies reported on program implementation, barriers, risk factors, and/or strategies related to stunting reduction in Papua. A total of 45 studies met the inclusion criteria and were synthesized using a thematic narrative approach. The review indicated that stunting reduction efforts in Papua have included both nutrition-specific and nutrition-sensitive interventions, supported by the establishment of acceleration teams, the use of integrated health service posts (Posyandu), supplementary feeding, micronutrient supplementation, and the 1,000 days of life initiative. However, program effectiveness is constrained by geographical isolation, health workforce shortages, weak cross-sectoral coordination, and a persistent gap between national policy design and local implementation capacity. Frequently reported risk factors included suboptimal caregiving practices, inadequate dietary intake, recurrent infections, poor sanitation, poverty, and a double burden borne by women, all of which impede program success. Conversely, locally grounded strategies—such as local food-based interventions, strengthening cadres and traditional leaders, community education, and pentahelix collaboration—emerged as more contextually appropriate and community-accepted approaches. Overall, these findings underscore the need to adapt policies to local conditions, strengthen convergence governance, and expand long-term evaluative research to improve the effectiveness and sustainability of stunting interventions in Papua’s 3T regions.